Intensitas Mengakses Tik-Tok dan Electronic Word of Mouth: Perannya Terhadap Pembelian Impulsif - Cyntia Wahyu Auliasari; Lucky Ade Sessiani; Siti Hikmah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Impulsive buying is a purchase that is caused by an emotional impulse that arises in the moment and is carried out spontaneously, without planning and without thinking about the consequences after the purchase of a product. The purpose of this study is to empirically test the intensity of access to Tik-Tok and electronic word of mouth: their role in impulse buying. The method used is quantitative with non-probability sampling techniques. The sample of this study came from young adults, a total of 354 people between the ages of 19 and 35. While the data analysis technique used in this study is the classical assumption test and hypothesis testing, which is processed with the help of SPSS software version 25. The results of the analysis show that the intensity of access to Tik-Tok and electronic word-of-mouth partially plays a significant role in impulse buying. At the same time, it shows that the intensity of access to Tik-Tok and electronic word of mouth plays a role of 29.4% on impulsive buying and 70.6% is influenced by variables outside this study. This study suggests that young adults reduce the intensity of access to Tik-Tok and electronic word of mouth in order to avoid impulsive buying behaviour